2022
DOI: 10.3390/jmse10121921
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination and Ecological Risk Assessment in the Sediment Cores of the Wetlands in Southern Thailand

Abstract: The concentration and distribution of trace metals were determined in sediment cores from the Khuan Khi Sian wetland, Thailand. The sediment cores were collected from seven stations in the dry and wet seasons in 2022. The concentration of Pb, As, and Cd in the dry season were in the range 0.00–60.16, 0.00–6.68, and 0.00–0.92 mg/kg (dry weight), respectively. Meanwhile, the concentration of Pb, As, and Cd in the wet season were in the range 0.00–12.12, 0.00–3.86, and 0.00–0.92 mg/kg (dry weight), respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In the aquatic environment, heavy metals can be very toxic to aquatic life and the human population due to their persistence, toxicity, non-degradability, bioaccumulation, and biomagnification in the food chain [ 81 , 82 ]. Heavy metals can enter the human body through the oral, inhalation, and dermal contact routes [ 83 ]. Exposure to high doses of heavy metals can induce complications in the human system, such as nausea, vomiting, diarrhea, kidney failure, neurological changes, Alzheimer’s disease, cardiovascular disease, and cancer [ 84 ].…”
Section: Socio-environmental Impacts and Risks Generated By Mine Tail...mentioning
confidence: 99%
“…In the aquatic environment, heavy metals can be very toxic to aquatic life and the human population due to their persistence, toxicity, non-degradability, bioaccumulation, and biomagnification in the food chain [ 81 , 82 ]. Heavy metals can enter the human body through the oral, inhalation, and dermal contact routes [ 83 ]. Exposure to high doses of heavy metals can induce complications in the human system, such as nausea, vomiting, diarrhea, kidney failure, neurological changes, Alzheimer’s disease, cardiovascular disease, and cancer [ 84 ].…”
Section: Socio-environmental Impacts and Risks Generated By Mine Tail...mentioning
confidence: 99%
“…Various methods have been employed to measure the extent of heavy metal pollution in sediment, including the enrichment factor (EF) and contamination factor (CF) (Sutherland, 2000;Mandal et al, 2022). Iron (Fe) is considered a more cautious normalizer (Pradit et al, 2022). The selection of appropriate background values is crucial for accurately interpreting geochemical data.…”
Section: Indices For Contamination Level Assessmentmentioning
confidence: 99%
“…Consequently, the presence of heavy metals has significantly increased due to human activities 9 . Monitoring studies in Thailand have revealed heavy metal contamination in diverse environments such as coastal areas, farmland, wetlands, mining areas, industrial zones, rivers, and estuaries 10 . The extensive impact is attributed to over 30,000 industrial establishments in the Chao Phraya River basin, contributing to river water pollution with harmful substances, including heavy metals discharged from industrial effluents 11 , This widespread environmental impact is observed across various ecosystems.…”
Section: Introductionmentioning
confidence: 99%